2018
DOI: 10.1172/jci.insight.96492
|View full text |Cite
|
Sign up to set email alerts
|

Intracapillary immune complexes recruit and activate slan-expressing CD16+ monocytes in human lupus nephritis

Abstract: Lupus nephritis is a major cause of morbidity in patients with systemic lupus erythematosus. Among the different types of lupus nephritis, intracapillary immune complex (IC) deposition and accumulation of monocytes are hallmarks of lupus nephritis class III and IV. The relevance of intracapillary ICs in terms of monocyte recruitment and activation, as well as the nature and function of these monocytes are not well understood. For the early focal form of lupus nephritis (class III) we demonstrate a selective ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 70 publications
3
38
0
Order By: Relevance
“…We found a higher production of cytokines associated with the development of Th1 (IL-2, IFN-γ, and TNF-α), Th2 (IL-5), and Th17 (IL-17) profiles, suggesting that CD32 ligation does not promote a particular signature in CD4+ T cells. Because ICs are the most important ligands for FcγRs, our observations might be relevant in those disorders associated with the presence of high levels of circulating ICs, such as chronic infections ( 45 47 ), autoimmune diseases ( 48 51 ) and cancer ( 52 54 ). Our results suggest that ICs might promote the development of inflammatory responses, by acting directly on CD4+ T cells via CD32a.…”
Section: Discussionmentioning
confidence: 95%
“…We found a higher production of cytokines associated with the development of Th1 (IL-2, IFN-γ, and TNF-α), Th2 (IL-5), and Th17 (IL-17) profiles, suggesting that CD32 ligation does not promote a particular signature in CD4+ T cells. Because ICs are the most important ligands for FcγRs, our observations might be relevant in those disorders associated with the presence of high levels of circulating ICs, such as chronic infections ( 45 47 ), autoimmune diseases ( 48 51 ) and cancer ( 52 54 ). Our results suggest that ICs might promote the development of inflammatory responses, by acting directly on CD4+ T cells via CD32a.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, this is the first study investigating the role of slan + DC in T1D. slan-expressing monocytes are in nephropathy in lupus erythematosus [21], is needed. 1f).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the fact that no other differences between patient subgroups and controls were found, further investigations into whether the slan + DC subset may be a predictor for the development of T1D complications, e.g. slan-expressing monocytes are in nephropathy in lupus erythematosus [21], is needed.…”
Section: Discussionmentioning
confidence: 97%
“…[47][48][49][50][51] More recently, in vitro work has shown that interactions between CD16 on CD16 hi human monocytes and immune complexes recruit CD16 hi monocytes from the circulation to the vascular interface of glomerular capillaries and induce the subsequent inflammatory response. 52 In rats, there are no CD16 knockout strains or blocking antibodies available. However, a polymorphism in the Fcgr3 genetic locus is responsible for a large part of the enhanced susceptibility of WKY rats to NTN, compared with NTN-resistant Lewis rats, which have an identical MHC haplotype but lack this polymorphism.…”
Section: Discussionmentioning
confidence: 99%